P23 'This is a policy not a pilot': how to implement routine opt-out HIV testing for acute medical admissions in an NHS trust in a high prevalence area. (23rd May 2012) - Barbour, A; Elgalib, A; Draper, S; Phillips, D R
Abstract : Background and Aims: Feasibility and acceptability of HIV testing in acute medical settings has been demonstrated in pilot studies. Whereas we report our success of embedding HIV testing in routine clinical care, delivered and sustained by medical staff in an NHS trust. Methods: From July 2011 all patients aged 16–79 years, attending the Acute Medical Unit (AMU), have had a standard HIV test unless they decline. Laboratory costs are funded by the local NHS. Literature was produced for staff and patients. Verbal consent and test ordering is carried out by general medical doctors and AMU nurses, all had training by the local HIV team. AMU proformas were updated with sections for HIV test offer and reason for refusal. The HIV team made regular AMU visits to motivate, troubleshoot and feedback progress. From the outset, nurses were more proactive than doctors in applying the policy. Building on their enthusiasm, nurses were empowered so that by October 2011 AMU visits were weaned as nurses took the lead to enforce the policy. Results: 3709 attendees in the first 6 months, median age 57 years, 50% female, 54.7% Caucasian, 6% Black African. 1390 (37.5%) had samples for HIV testing; their demographic profile is comparable to that for all attendees. HIV test rate went from 33.2% July–September to 41.3% October–December (p<0.005 χ 2 ). For a random sample (n=396), HIV test uptake was 84%. Detailed analysis on offer rate and factors associated with uptake will be presented at the conference. Seven new HIV diagnoses were made, all but one had CD4 >200. Conclusion: A routine opt-out HIV testing policy can be delivered by frontline medical staff in an acute setting with no extra resource requirement beyond laboratory costs. Such a policy identifies new HIV patients who would not otherwise have tested and reduces late diagnosis. We believe that policy ownership by nurse champions, with the HIV team as background advisors, is key to achieving and sustaining high test rates.